Free Fatty Acids Activate Renin-Angiotensin System in 3T3-L1 Adipocytes through Nuclear Factor-kappa B Pathway - Jia Sun; Jinhua Luo; Yuting Ruan; Liangchang Xiu; Bimei Fang; Hua Zhang; Ming Wang; Hong Chen (Journal of Diabetes Research)
The activity of a local renin-angiotensin system (RAS) in the adipose tissue is closely associated with obesity-related diseases. However, the mechanism of RAS activation in adipose tissue is still unknown. In the current study, we found that palmitic acid (PA), one kind of free fatty acid, induced the activity of RAS in 3T3-L1 adipocytes. In the presence of fetuin A (Fet A), PA upregulated the expression of angiotensinogen (AGT) and angiotensin type 1 receptor (AT1R) and stimulated the secretion of angiotensin II (ANG II) in 3T3-L1 adipocytes. Moreover, the activation of RAS in 3T3-L1 adipocytes was blocked when we blocked Toll-like receptor 4 (TLR4) signaling pathway using TAK242 or NF-κB signaling pathway using BAY117082. Together, our results have identified critical molecular mechanisms linking PA/TLR4/NF-κB signaling pathway to the activity of the local renin-angiotensin system in adipose tissue.